2023
DOI: 10.3389/fmicb.2023.1141378
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol in food and feed: Recent advances in decontamination strategies

Abstract: Deoxynivalenol (DON) is a mycotoxin that contaminates animal feed and crops around the world. DON not only causes significant economic losses, but can also lead diarrhea, vomiting, and gastroenteritis in humans and farm animals. Thus, there is an urgent need to find efficient approaches for DON decontamination in feed and food. However, physical and chemical treatment of DON may affect the nutrients, safety, and palatability of food. By contrast, biological detoxification methods based on microbial strains or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…In this regard, advanced decontamination strategies for reductions in DON, ZEA, and T-2/HT-2 in feed for swine, poultry, and rabbits should be developed and applied. In this regard, effective treatments for removing/detoxifying DON in animal feed based on ion-exchanged zeolites absorption [ 37 ], Rhodotorula glutinis, B. subtilis ZZ, and other microorganism and enzymatic actions [ 38 , 39 ], and ozone [ 40 ] were reported during recent years [ 41 ]. With regard to ZEA, interesting approaches to its removal from animal feed based on L. plantarum BCC 47723 [ 42 ] and conidia of Aspergillus japonicus [ 43 ] activities were recently published.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, advanced decontamination strategies for reductions in DON, ZEA, and T-2/HT-2 in feed for swine, poultry, and rabbits should be developed and applied. In this regard, effective treatments for removing/detoxifying DON in animal feed based on ion-exchanged zeolites absorption [ 37 ], Rhodotorula glutinis, B. subtilis ZZ, and other microorganism and enzymatic actions [ 38 , 39 ], and ozone [ 40 ] were reported during recent years [ 41 ]. With regard to ZEA, interesting approaches to its removal from animal feed based on L. plantarum BCC 47723 [ 42 ] and conidia of Aspergillus japonicus [ 43 ] activities were recently published.…”
Section: Discussionmentioning
confidence: 99%
“…A recent assessment of mycotoxin contamination found that the concentration of DON in most tested food samples exceeded the prescribed limits . Many countries around the world have DON contamination rates of more than 80% in food commodities, including China, Sweden, Italy, Brazil, and South Africa . On a regular basis, food consumption exposes humans to DON.…”
Section: Introductionmentioning
confidence: 99%
“…DON, a tetracyclic sesquiterpenoid type B trichothecene is predominantly produced by F. culmorum and F. graminearum during the infection of corn, wheat, oats, barley, and rice [6,7]. Ingestion of DON through the consumption of infected feed by animals can lead to diarrhea, vomiting and gastroenteritis, arising from the inhibition of protein translation via interference with peptidyl transferase function on the ribosome as well as by modifying gene expression, culminating in cellular death [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion of DON through the consumption of infected feed by animals can lead to diarrhea, vomiting and gastroenteritis, arising from the inhibition of protein translation via interference with peptidyl transferase function on the ribosome as well as by modifying gene expression, culminating in cellular death [8]. Various modified analogs of DON are reported, where modifications that include the acetylation, glycosylation, de-epoxidation, epimerization and hydroxylation of DON and DON derivatives are associated with enzymatic activity in plant hosts or by other microbial species that have evolved a protective strategy to detoxify DON [2,7]. With anticipated increases in the spread of toxigenic fungal species due to climate change, understanding the underlying DON detoxification mechanisms has become a priority based on the adverse health effects noted above.…”
Section: Introductionmentioning
confidence: 99%